(untitled) (Comprehensive Journal of Science, 2025)
This study was conducted in the Poultry Laboratory of the Animal Production Department, Faculty of Agriculture – Omar Al-Mukhtar University, in Al-Bayda City, of the autumn season of 2023. The aim was to evaluate the quality of eggs circulating in local markets by comparing three production sources: Tamam Company eggs (improved breeds), local commercial eggs, and local (National) chicken eggs (Al- watani). A total of 150 eggs were randomly collected, with 50 eggs from each source, and all underwent measurements including weight, shell thickness, albumen height (to calculate Haugh unit), yolk height, diameter, and color score. The results showed significant differences among the three sources. Tamam Company eggs significantly excelled in weight (74.40 g) and shell thickness (0.36 mm), in addition to their superiority in yolk color score and diameter. In contrast, local commercial eggs recorded the highest yolk height, while local (Baladi/National) eggs showed the highest significant value for Haugh unit (91.72), followed by commercial eggs, and then Tamam Company eggs. The study concluded that the superiority of Tamam Company eggs in some physical characteristics may be attributed to genetic makeup (breed) and feed quality, while local (Baladi/National) eggs demonstrated distinct internal quality, particularly in terms of albumen freshness. Commercial eggs also showed a clear advantage in yolk height.